1994
DOI: 10.1002/bip.360341010
|View full text |Cite
|
Sign up to set email alerts
|

The potential energy surface of methyl 3‐O‐(α‐D‐mannopyranosyl)‐α‐D‐mannopyranoside in aqueous solution: Conclusions derived from optical rotation

Abstract: SYNOPSISThe optical rotation of methyl 3'0-(a-D-mannopyranosyl) -a-D-mannopyranoside is calculated semiempirically as a function of the linkage dihedral angles 4 ( H1-C1-01-C3') andComparison with the observed optical rotation in aqueous solution indicates the existence of at least two conformers in solution, which implies a degree of linkage flexibility. The result is in agreement with some, but not all, calculated potential energy surfaces, and with recently published nmr data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

1995
1995
2001
2001

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 36 publications
2
4
0
Order By: Relevance
“…Beginning with the III-OCH 3 linkage, these authors noted a discrepancy in measured correlation times for the methyl group and postulated that this could arise from additional motions of this group that were not included in their treatment of the data. More recently, results of optical rotation studies on methyl ␣-D-mannopyranoside found that including a population of a ϭ 180°state of 10 -20% (in addition to the ϭ 60°s tate) for the methoxy linkage was able to bring the calculated values of the molar rotation into agreement with those experimentally observed (Stevens et al, 1989;Stevens, 1994). These results agree well with our model, which supports a minor population of a ϭ 150°state of less than 35%.…”
Section: Comparison To Similar Structuressupporting
confidence: 90%
See 1 more Smart Citation
“…Beginning with the III-OCH 3 linkage, these authors noted a discrepancy in measured correlation times for the methyl group and postulated that this could arise from additional motions of this group that were not included in their treatment of the data. More recently, results of optical rotation studies on methyl ␣-D-mannopyranoside found that including a population of a ϭ 180°state of 10 -20% (in addition to the ϭ 60°s tate) for the methoxy linkage was able to bring the calculated values of the molar rotation into agreement with those experimentally observed (Stevens et al, 1989;Stevens, 1994). These results agree well with our model, which supports a minor population of a ϭ 150°state of less than 35%.…”
Section: Comparison To Similar Structuressupporting
confidence: 90%
“…Later studies using MD simulations, both in vacuo (Balaji et al, 1994) and including explicit solvent (Homans, 1990), along with other studies using proton relaxation measurements in partially deuterated samples (Hricovíni et al, 1992) all found evidence of internal motion at this linkage, suggesting that both of the previously identified states may be sampled in solution. More recent studies using optical rotation techniques (Stevens, 1994), molecular mechanics modeling (Dowd et al, 1995), and circular dichroism (Arndt and Stevens, 1996) have indeed concluded that states near (80°, Ϫ160°) and (80°, Ϫ80°) are likely to be equally populated in solution. These studies also predicted a small population (ϳ10%) of a state near (160°, Ϫ80°).…”
Section: Comparison To Similar Structuresmentioning
confidence: 99%
“…The current solvated MD data indicate that the A-(1→3) linkage between A-4′ is more flexible than the 4-3 linkage, as we would expect that the more internal location of the 4-3 linkage within Man 9 GlcNAc 2 would make it more inflexible. Flexibility of the A-(1→3) linkage in the related mannose disaccharide is consistent with experimental optical rotation measurements [36]. A crude estimate of the increased flexibility of the A-4′ linkage is provided by the relatively high values for the standard deviations in the values of the glycosidic angles (Ϫ22Ϯ 22°, Ϫ30Ϯ 16°) for this linkage.…”
Section: Conformational Analysis By Molecular Dynamics Simulationsupporting
confidence: 83%
“…Oligosaccharides containing α-linked mannose residues have previously been studied by molecular modeling in both vacuum and water . Modeling studies have also been combined with NMR relaxation, , optical rotation, and X-ray crystallography data . The results from these studies indicate that a predominant conformation exists for both the α(1→2) and the α(1→3) linkages, but minor populations of other conformers could not be ruled out on the basis of the experimental data used.…”
Section: Introductionmentioning
confidence: 99%